As políticas sustentáveis desenvolvidas por diferentes empresas para a preservação da biodiversidade e dos polinizadores - Astolfo, Tauane de Lima (Universidade Federal de São Carlos, 2021)
The importance of biodiversity only gained greater prominence when the process of loss of biological diversity raised awareness of the need for conservation and rational use of living resources, with protection of the flow of services from natural ecosystems. The preservation of biodiversity has economic reasons when it is thought that its degradation can harm existing activities, such as agriculture, for example, which could compromise its use in the future since many of the foods produced today for consumption and sale are dependent on pollination, the resulting ecosystem service of biodiversity. In this aspect, pollinators are extremely linked to ecological relationships in the environment and play very important roles in the conservation, maintenance and specialization of biodiversity. However, in recent years it has been found that pollinator populations are declining, threatened by anthropogenic changes caused in natural ecosystems, such as agriculture, an area that is on the rise. Therefore, the present study aimed to carry out a survey on the websites of companies that produce pesticides and food with little, modest, high and essential dependence on pollination to understand whether they have sustainable policies for the preservation and conservation of biodiversity and, consequently, pollinators. The results found were tabulated and analyzed graphically to verify the preservation of biodiversity and pollinators as an essential component for the maintenance of the environment. Thus, the information obtained in this study was of great relevance, since it was possible to observe that most companies are concerned, in some way, with the preservation of the environment. However, pollinators are not a concern on the agenda for many companies, whether they are producers of food or pesticides. Thus, this study provides further support for the continuation of work regarding the concern of companies that may cause direct or indirect impacts on the preservation of biodiversity and, consequently, on pollinators.
Sustainable policies developed by different companies for the preservation of biodiversity and pollinators
Keywords: Empresas; Agrotóxicos; Alimentos; Polinização; Companies; Pesticides; Food; Pollination; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA